Review of Treatment of Common Body Disorders by Sound Therapy - Mittal, Vikas; *, Dixit (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Human beings spread out certain range of measurable frequencies. The level of these radiating frequencies varies with different states of the body’s health or illness. This paper demonstrates that each illness/disorder in the human body has different frequency that is always within a definite range and also implies the fact that the human body responds to various beneficial input frequencies given in the form of direct external light and sound. The ill body cells react to very precise levels of frequencies and get cured or eliminated whilst nearby healthy cells remained intact. Thus certain input frequency signals can help to improve physical health and can be used in the treatment various body illnesses. The general human healthy frequency is within the range of 62-72 Hz and when it drops to lower levels it enables the appearance of a variety of diseases. For example at the level of 58 Hz, diseases like cold and flu were more likely to appear. At much lower levels (42 Hz) fatal diseases like Cancer appear in humans and below, whilst death begins at 20 Hz.